Character Education KH. Bisri Mustofa’s Perspective in Syi’ir Mitra Sejati at Madrasah Diniyah - Saifudin; Abdul Ghofur (Rihlah Review: Jurnal Pendidikan Islam, 2023)
This study examines the values of character education contained in the book Syi'ir Mitra Sejati by Bisri Mustofa. This research is expected to be able to contribute scientific thinking about the relevance of educational values contained in the book Mitra Sejati. This research is descriptive qualitative research based on the case of study. Data collection techniques by collecting existing data either through observation, interviews, and documentation. The analytical method in this study uses two methods, namely the method of content analysis and the method of interpretive description. The results of this study explain that the book of Syair Mitra Sejati by KH. Bisri Mustofa contains the concept of moral education which has a social scope of humanity with several morals: morals to parents, people's morals to the government, morals of students to teachers, morals to friends, kinds of manners, morals of listening to conversations, morals of speaking, morals of associating, morals when eating, morals in dressing, caring for the environment, morals for visiting, morals to visit sick people.